ANALISIS YURIDIS KEABSAHAN PEMBEBANAN HAK TANGGUNGAN SEBIDANG TANAH YANG DIPEROLEH MELALUI JUAL BELI (STUDI PUTUSAN NOMOR 90/PDT.G/2021/PN.JKT.SEL): Juridical Analysis of the Validity of Mortgage Encumbrance on Land Acquired Through Sale (Case No. 90/PDT.G/2021/PN.JKT.SEL) - Dina Febryan; Dyah Setyorini (Faculty of Law, Universitas Trisakti, 2025)
The sale and purchase occur between the seller, who has the authority to transfer the rights to the land. The Grantor of the Mortgage Rights must have legal authority over the land object used as collateral. However, in practice, deviations occur in the implementation of the sale and purchase and the imposition of Mortgage Rights, as seen in Decision No. 90/PDT.G/2021/PN.JKT.SEL. The problem formulation is how to assess the validity of the imposition of mortgage rights on a piece of land acquired through sale and purchase in Decision No. 90/PDT.G/2021/PN.JKT.SEL. A normative juridical, descriptive-analytical method was used in this research. This study relies on secondary data from primary legal materials, which are analyzed qualitatively. Therefore, the results can be concluded deductively. The findings show that in Decision Number 90/PDT.G/2021/PN.JKT.SEL, the land was sold by a party who was not the legitimate owner, and the sale transaction was not carried out before an authorized Land Deed Official (PPAT), but only by a notary. As a result, the material and formal requirements for a valid land sale were not fulfilled. The conclusion is that all legal actions related to the land, including the sale and purchase and the imposition of Mortgage Rights, were declared invalid, and the land remains the property of the Plaintiff.